Phase I Study of the Novel Enhancer of Zeste Homolog 2 (EZH2) Inhibitor GSK2816126 in Patients with Advanced Hematologic and Solid Tumors - Yap, Timothy A. (Clin Cancer Res, 2019)
PURPOSE: Enhancer of zeste homolog 2 (EZH2) activity is dysregulated in many cancers. PATIENTS AND METHODS: This phase I study determined the safety, maximum-tolerated dose (MTD), pharmacokinetics, and pharmacodynamics of the intravenously administered, highly selective EZH2 inhibitor, GSK2816126, (NCT02082977). Doses of GSK2816126 ranged from 50 to 3,000 mg twice weekly, and GSK2816126 was given 3-weeks-on/1-week-off in 28-day cycles. Eligible patients had solid tumors or B-cell lymphomas with no available standard treatment regimen. RESULTS: Forty-one patients (21 solid tumors, 20 lymphoma) received treatment. All patients experienced ≥ 1 adverse event (AE). Fatigue [22 of 41 (53.7%)] and nausea [20 of 41 (48.8%)] were the most common toxicity. Twelve (32%) patients experienced a serious AE. Dose-limiting elevated liver transaminases occurred in 2 of 7 patients receiving 3,000 mg of GSK2816126; 2,400 mg was therefore established as the MTD. Following intravenous administration of 50 to 3,000 mg twice weekly, plasma GSK2816126 levels decreased biexponentially, with a mean terminal elimination half-life of approximately 27 hours. GSK2816126 exposure (maximum observed plasma concentration and area under the plasma-time curve) increased in a dose-proportional manner. No change from baseline in H3K27me3 was seen in peripheral blood mononuclear cells. Fourteen of 41 (34%) patients had radiological best response of stable disease, 1 patient with lymphoma achieved a partial response, 21 of 41 (51%) patients had progressive disease, and 5 patients were unevaluable for antitumor response. CONCLUSIONS: The MTD of GSK2816126 was established at 2,400 mg, but the dosing method and relatively short half-life limited effective exposure, and modest anticancer activity was observed at tolerable doses.